The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1034/j.1600-0773.2002.910207.x
|View full text |Cite
|
Sign up to set email alerts
|

Dose Response of Carboplatin‐Induced Nephrotoxicity in Rats

Abstract: Carboplatin, a second-generation platinum-containing anticancer drug, is currently being used against a variety of cancers. High-dose carboplatin chemotherapy can cause renal tubular injury in cancer patients. However, the biochemical mechanism of carboplatin-induced renal injury has not been well studied. This study investigated the dose response of carboplatin-induced changes in endogenous antioxidants, lipid peroxidation and platinum content in rat kidney. Male Wistar rats (250-300 g) were divided into five… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 36 publications
0
6
0
2
Order By: Relevance
“…The antioxidant enzymes are the first line of defence against free radical/ROS-induced oxidative renal injury [25]. Oxygen free radicals and hydroperoxides are produced in the organism via oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…The antioxidant enzymes are the first line of defence against free radical/ROS-induced oxidative renal injury [25]. Oxygen free radicals and hydroperoxides are produced in the organism via oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, measuring TBARS, SOD, GST, GPx, CAT, and TAC (Table 8) showed significant decrease in the levels of TBARS and increase in the activities of antioxidant enzymes (SOD, GST, GPx, CAT, and TAC) and the level of GSH compared to the control group (p > 0.05). Journal of Food Quality Antioxidant enzymes are the body defense mechanism for scavenging the free radicals that induce oxidative liver injury [59].…”
Section: In Vivo Studymentioning
confidence: 99%
“…This is one of the dose-limiting adverse effects related to clinical use of carboplatin. Several studies have shown that carboplatin administration can lead to dose-dependent nephrotoxicity in rodents and human beings specifically leading to acute tubular necrosis (Haschke et al, 2010;Husain et al, 2002Husain et al, , 2004. We have tried to corroborate these findings in rats treated with an overdose of carboplatin and tried to correlate carboplatin-induced renal damage to that of impairment of renal function observed in experimentally induced Fanconilike syndrome.…”
Section: Discussionmentioning
confidence: 65%